Emerging evidence of Urolithin A in sports nutrition: bridging preclinical findings to athletic applications - Wang, Manda; Yu, Liang (Frontiers in Nutrition, 2025)
Urolithin A (UA), a gut microbiota-derived metabolite of ellagic acid and ellagitannins, is emerging as a novel sports nutrition supplement with multifaceted benefits. UA demonstrates osteoprotective effects through dual regulation of bone remodeling, delays joint degeneration by reducing synovial inflammation, and enhances muscle endurance and peak oxygen uptake. Mechanistically, UA enhances mitochondrial β-oxidation and potentially activating skeletal muscle adenosine 5′-monophosphate-activated protein kinase (AMPK) signaling and upregulating mitochondrial respiratory chain complex activity to exert ergogenic effects. Notably, the benefits of UA seem to be unaffected by diet. We propose once-daily dosing with tentative pre-exercise timing, though exercise’s impact on UA pharmacokinetics requires further investigation. While UA’s multifunctionality bridges gaps in conventional sports supplements, human trials validating ergogenic claims—particularly regarding muscle-specific adaptations and metabolic system modulation—remain critical. This synthesis positions UA as a promising yet incompletely characterized candidate in sports nutrition, warranting rigorous translational research.